A (im)postura professoral no espaço da sala de aula : seus efeitos no ensino e na aprendizagem de escrita em Língua Portuguesa - Marinho, Mariana da Silva (2015)
This work was developed from our theoretical affiliation to studies undertaken by Émile Benveniste about the language and its operation, whose emphasis is the relationship between (inter) speakers. This filiation was relevant because we intend to think the relation teacher-student-know, from the problematization of a teacher in the classroom with professoral (im)posture in relation to teaching writing in Portuguese. The starting point of differentiation established by Benveniste (2014) between writing and written language, the language being understood as the written language under its written form and writing as an enunciative act that requires the speaker-scriptor the apropriation of the writing language and your handling, so that it is possible (between) see a trace of subjectivity in its written and so that he canspell out, in writing, of his position and produce senses. When looking at the occurrence ways on teaching writing in Portuguese and in a class of students in the 5th year of elementary school, I understand that, in most cases the relation of these students with writing is still frail, including by aspects of the relation to the writing time. For these students, the learning of writing demand the teacher a continuous intervention plan. What would be expected is that the teaching of writing in Portuguese occur, then, so that the teacher make possible the loop intensification of students with the related knowledge to writing, for the chance of transmission takes place at school, and the his teaching could, thereby, carry up in some measure. As for the methods we use to do the problematization proposal, they do not constitute closed instruments while whose concepts serve to the application of theory, but seek to build the categories of analysis from our goal, which was to understand and explain the operation the discursive relation established between teacher and students in teaching writing in Portuguese classroom from the text production. The mo(ve)ments analysis we seek to undertake are based on clippings of interviews with the teacher, the materials used by it in the textual production of proposals, the classes where the demands of writing occurred and four (04) textual productions students. By the look that launched to these materials, we were able to discuss the pedagogical actions of the teacher, as well as its (un)liability with the teaching of writing in Portuguese affect the teacher-student- know, so that, depending on the frail relation the teacher maintains itself with the teaching of writing in Portuguese and their own writing, she can not intensify the relationship of students with this knowledge in order to promote significant changes in their mo(ve)ments of writing.